Cross sections data adjustment for KRITZ-2:13 - Abdulaziz Ahmed; H. Boukhal; E. Chakir; S. EL Ouahdani (Kuwait Journal of Science)
Over the past years, the cross-sections reaction data has been re-evaluated several times, in order to approximate the nuclear model measurements with the predictions with great reliability. In our work, uncertainty analysis caused by the data on the neutron factor (Keff) and the reactivity temperature coefficient (RTC), in addition to nuclear data adjustment have been done for KRITZ-2:13 reactor, with ENDF/B - VII.1, ENDF/B - VIII.0 and JENDL - 4.0 evaluations by the nuclear code MCNP6.1. Our analysis detects that the greatest uncertainty on Keff and RTC in the studied libraries comes from the capture and fission reaction contributions respectively, for U-238 and U-235. The previous reactions and their covariances were adjusted using the generalized least squares method (GLLSM), in order to contribute to improve the data needed for neutron simulation of experiments and to ensure the installations safety, where Keff and RTC represent neutron parameters reflecting the modification effects in the data.